Creating claustrophobia in Christopher Nolan’s Dunkirk - Lankauskaitė, Viktorija (Creativity Studies, 2023)
Christopher Nolan’s cinema and its immersive quality is appreciated by audiences and critics alike, and already analysed by researchers, often mentioning “claustrophobia” as a feeling encountered in his films. However, a number of extensive explorations of his work, and filmmaking in general, leave the creation of claustrophobia in cinema undiscussed. Thus, the article aims to fill the gap and investigate his 2017’s film Dunkirk, since this account of the historical event during the World War II has often been described as “claustrophobic”. Cinematic space and time, the way the medium can be used to create certain feelings, as well as the properties of Nolan’s work are examined. Space and time manipulation, the use of IMAX for immersion, interchanging aspect ratios, and the idea of contrasts are responsible for the claustrophobic atmosphere in the film. The study could be useful for filmmakers and creatives, as well as for audiences interested in what shapes their experience of the story they see on screen.